2010 IEEE 25th Annual Conference on Computational Complexity 2010
DOI: 10.1109/ccc.2010.31
|View full text |Cite
|
Sign up to set email alerts
|

The Partition Bound for Classical Communication Complexity and Query Complexity

Abstract: In this work we introduce, both for classical communication complexity and query complexity, a modification of the partition bound introduced by Jain and Klauck [JK10]. We call it the public-coin partition bound. We show that (the logarithm to the base two of) its communication complexity and query complexity versions form, for all relations, a quadratically tight lower bound on the public-coin randomized communication complexity and randomized query complexity respectively.The partition bound introduced by Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(109 citation statements)
references
References 37 publications
2
107
0
Order By: Relevance
“…The definition of the corruption bound Corr( f ) is given in Section 3, but for now, we note that Corr( f ) essentially depends on the size of the largest approximately 1-monochromatic rectangle in the communication matrix of f . (For an extensive discussion of the different lower bound methods in communication complexity, see [24].) Previously, Klauck [29] showed that Corr( f ) lies somewhere between the MA and AM communication complexities of f ; namely…”
Section: Results For Sbp and Usbpmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of the corruption bound Corr( f ) is given in Section 3, but for now, we note that Corr( f ) essentially depends on the size of the largest approximately 1-monochromatic rectangle in the communication matrix of f . (For an extensive discussion of the different lower bound methods in communication complexity, see [24].) Previously, Klauck [29] showed that Corr( f ) lies somewhere between the MA and AM communication complexities of f ; namely…”
Section: Results For Sbp and Usbpmentioning
confidence: 99%
“…A lot of effort (e. g., [29,24,28,25,19]) has been spent on comparing the relative strengths of different lower bound methods in communication complexity with the goal of finding a natural method that captures the bounded-error randomized communication complexity of every function. Theorem 1.1 can be viewed as achieving a diametrically opposite goal: we THEORY OF COMPUTING, Volume 12 (9), 2016, pp.…”
Section: Results For Sbp and Usbpmentioning
confidence: 99%
“…recently, the lower bounds of [47] have been shown [27] to not apply to the partition bound technique of Jain and Klauck [35].…”
Section: Proof 2: Using Information Cost Direct Sum (Sketch)mentioning
confidence: 99%
“…Settling this claim requires the introduction of a second measure, call it λ , to account for covering by large rectangles. The smooth rectangle bound [9] was discovered very recently and overcomes limitations of Yao's corruption bound-at the expense of being more challenging to use.…”
Section: Previous Workmentioning
confidence: 99%
“…The authors actually derive a much stronger statement, giving a detailed characterization of the distribution of x, y . To complete the proof, they use a criterion for high communication complexity due to Jain and Klauck [9], known as the smooth rectangle bound. Specifically, Chakrabarti and Regev use their anticoncentration result to argue that in any partition of R n × R n , only a small constant measure of inputs can be covered by large uncorrupted rectangles.…”
Section: Previous Workmentioning
confidence: 99%